Patient-Controlled Intravenous Analgesia with or without Ultrasound-Guided Bilateral Intercostal Nerve Blocks in Children Undergoing the Nuss Procedure: A Randomized, Double-Blinded, Controlled Trial. (22nd July 2022) - Ma, Bingjie; Sun, Yuan; Hao, Can; Liu, Xiaoming; Shen, Sai'e
Abstract : Background . Two analgesic strategies have been described for pain treatment after the pectus excavatum surgery: the patient-controlled intravenous analgesia (PCIA) and ultrasound-guided intercostal nerve block. In this prospective, randomized and double-blinded trial and the short and long-term outcomes were compared in patients after surgery. Methods . The children were randomized to either the intercostal or control group. Ultrasound-guided intercostal nerve block was with 0.25% ropivacaine and 5 mg dexamethasone in the intercostal group, while the control group was with 0.9% normal saline. The block was performed in the intercostal space corresponding to the lowest depression of the sternum and repeated bilaterally in the spaces above and below. Postoperatively, the children in the two-groups received PCIA with fentanyl for 48 hours. The primary outcome was a pain score on the postoperative day 1, as measured by the Visual Analogue Scale (VAS). Results . Sixty children undergoing the Nuss procedure were enrolled in the trial. The mean differences in VAS scores between the two groups were 3.2 in the PACU (p < 0.001 ), 1.7 on postoperative day 1 (p < 0.001 ) and 0.7 on postoperative day 2 (p = 0.015 ). The opioid consumption was significantly lower in the intercostal group during the postoperative 48 hours (p < 0.05 ). The anxiety and QOL scores in the intercostal group were significantly improved on some points of time (p < 0.05 ). The incidence of adverse events was markedly lower in the intercostal group during the postoperative 48 hours (p < 0.05 ). Conclusions . Our results suggest ultrasound-guided intercostal nerve block with PCIA may be more effective than PCIA alone in children who underwent the Nuss procedure.